INTERNAL DOSIMETRY IN NUCLEAR MEDICINE - Michael G. Stabin (Brazilian Journal of Radiation Sciences, 2013)
This article reviews the current state of the art in the calculation of radiation doses for radiopharmaceuticals. Basics of dose calculations are briefly reviewed, and the sources of input data for the calculations are reviewed. Although dose calculations are needed for all kinds of radiopharmaceuticals, dose calculations in therapeutic applications are the most important for the patient; the status of dose calculations for most important therapeutic uses of radiopharmaceuticals is discussed, and the importance of performing patient-individualized dose calculations is emphasized